Early Childhood Cognitive Development in The Book “Benda ajaib Di Dapur Nenek” By Hasta Indriyana - Nurjanah, Siti (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This paper contains an analysis of early childhood cognitive development illustrated through activities and interactions in a storybook entitled Benda Ajaib di Dapur Nenek by Hasta Indriyana. The main problem discussed is that it can contribute to early childhood cognitive development. Where currently the approach to learning through storybooks is rare and less popular. Several theories from Piaget, Vygotsky, Gardner, Bandura, and Bruner are referenced in the discussion. The results of this study conclude that local culture-based literacy reading contributes significantly to early childhood cognitive development. In addition to cognitive aspects, the story also supports children's social-emotional development through interactions with adult characters and overal the book can be a learning medium that is not only informative but also shapes children's character by introducing cultural, environmental and social values.